Effect of grain content on the nutritive value of whole-plant corn silage - R.N. Jr. Sonon; B.S. Dalke; D.L. Holthaus; L. Pfaff; K.K. Bolsen; Matthew A. Young (Kansas Agricultural Experiment Station Research Reports, 1994)
This experiment was conducted to determine the effect of grain content on the nutritive value of corn silage. Whole-plant silage dry matter (DM) increased, whereas neutral detergent fiber (NDF) and acid detergent fiber (ADF) contents decreased as the level of grain increased from 0 to 65% in the reconstituted, whole-plant, corn silages. Using sheep as a model, voluntary DM intake and DM and organic matter (OM) digestibility increased, but crude protein (CP) and ADF digestibilities decreased linearly as grain content increased from 0 to 52.5%. Our results indicate that the optimum level of grain in whole-plant corn silage to maximize the nutritive value of a high silage-based ration was about 52.5%.
Keywords: Cattlemen& #x27; s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Corn; Silage; Grain content; Nutritive value